The Use of Legal Maxims in the Fatwas of Indonesian Ulama Council - Mudzhar, Mohamad Atho (Graduate School of Syarif Hidayatullah State Islamic University Jakarta, 2022)
The increasing, often controversial, roles of the Indonesian Ulama Council or Majlis Ulama Indonesia (MUI) in society have attracted scholars to study the institution, including its fatwas and their arguments. This study examines how legal maxims (qawa'd fiqhiyyah) had been used to construct the arguments of MUI's fatwas. This study also identifies the legal maxims used, observes their frequencies, and determines the patterns of their application. Legal maxims are important since they show principles and logic to discover legal norms. Some 118 fatwas on ritual, Shariaheconomic, and socio-cultural issues are examined. This study found that 25 legal maxims had been used by the MUI's fatwas, with five being most frequently referred to. On average, each fatwa referred to 1.23 legal maxims. Fatwas on economic issues used most legal maxims with an average of 2.14, while those on socio-cultural and ritual issues used only 0.66 and 0.47 legal maxims on average, respectively. Fatwas on economic issues seemed to be the most dynamic ones.